2009
DOI: 10.1016/s0924-9338(09)70692-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Youth

Abstract: Introduction:In adolescence alcohol can become considerable psychological stimulus, and its more regularly consuming will be the first step in making psychological and later physical dependence as well.Method:The aim is to establish the freqsuency of misuse of alcohol among the youth and some of risk factors which precipitate that kind of behaviour.610 secondary school pupils (360 females and 250 males), aged 14 - 18, in Banja Luka were sampled. Selfreported Questionnaire of Risk Behaviour by K. Berg-Kelly (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Children's emotional reactions during the divorce can vary relative to the gender and age of the child. 1 Parental disharmony and quarrels before the divorce appears to be more detrimental to a child's adjustment than the separation itself, which may relieve tension. 6 Herein, we discussed marriage and marital fidelity, which determine the course of the interparental relationship, from a religious perspective to draw attention to the importance of the family institution in child health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's emotional reactions during the divorce can vary relative to the gender and age of the child. 1 Parental disharmony and quarrels before the divorce appears to be more detrimental to a child's adjustment than the separation itself, which may relieve tension. 6 Herein, we discussed marriage and marital fidelity, which determine the course of the interparental relationship, from a religious perspective to draw attention to the importance of the family institution in child health.…”
Section: Introductionmentioning
confidence: 99%
“…Family is crucial for the development of children. 1 Parents ensure children are healthy and safe, equip them with the skills and resources to succeed as adults, and transmit fundamental cultural values to them. Parents offer their children love, acceptance, appreciation, encouragement, and guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Il divorzio di un genitore non è necessariamente così negativo per i figli che possono superare la prova con successo, soprattutto se i genitori si comportano in modo adeguato. La possibilità di accedere serenamente a entrambi i genitori; sapere che entrambi continueranno a rispettarsi fra loro; la certezza che si occuperanno di figli e figlie con attenzione, mantenendo così la funzione genitoriale, senza strumentalizzazioni conflittuali, rendono tutto più sereno [7].…”
Section: Considerazioni Generaliunclassified
“…Often, children, especially those of pre-school or school age, blame themselves for the dissolution of their parents’ marriage, continuing to fantasise about a family reunion [ 13 , 14 , 15 ]. Several studies have shown that children of parents who are separated or in the process of divorce exhibit changes in mood, with increased sadness and anger [ 16 , 17 ] and lowered school performance [ 18 , 19 ]. Studies have shown that families in which there is a child diagnosed with autism spectrum disorder (ASD) are more likely to divorce than families of neurotypical children [ 20 ].…”
Section: Introductionmentioning
confidence: 99%